Teaching communication, skills and competencies for the international workplace a resource for teachers of English - Gimenez, Julio (Routledge, 2023)
"Backed by evidence and research, this practical book presents an innovative yet comprehensive approach to teaching non-native English speakers the main communication and cultural competencies that are required to succeed in an international English-speaking workplace. Each unit includes strategies for teaching key skills, tasks to encourage reflection and notes on relevant cultural and technological issues. Practical features in each unit include lesson plans and materials, insights from the research, extension tasks, reflection activities and further readings. Supported by current learning theories, key teaching methodologies and assessment materials, the chapters address the challenges that non-native English speakers may face in the international English-speaking workplace. Areas of focus include: Job hunting Job applications Interviews Interpersonal, written and spoken communication Performance appraisals Applying for promotions Written for pre-service, practicing and future teachers, with specific guidance for each role, this is an essential resource for all educators who want to confidently address the challenges that non-English speakers may encounter at work, including linguistic proficiency, cultural awareness and the use of technology"--